Produção de sentido de profissionais de uma ILPI sobre sexualidade e dissidências sexuais e de gênero - Marqueto, Fernanda Pires (2024)
Long-term care institutions for the elderly are part of the Unified Social Assistance System and aim to provide a space for living and institutional care for elderly individuals, whether they are in a situation of social vulnerability or not. Therefore, this study aims to investigate the meanings produced by professionals from a Long-Term Care Institution for the Elderly in a city in the interior of Minas Gerais regarding gender identity and sexual orientation of elderly people in care. The results revealed that the professionals at this particular LTCI reflect sexual norms based on a cis-heteronormative matrix. They are aware of some of the sexual identities represented by the LGBTQIA+ acronym, such as lesbian, gay, bisexual, and transgender identities, but are unfamiliar with queer, intersex, and asexual identities. When providing care to the residents of this space, there is also an influence of cis-heteronormativity, indicating that they view the course of life from a heteronormative teleological perspective. The results also show that the research participants produce LGBTphobia in their statements as symbolic violence against all sexual and gender dissidences, with a more accented focus on transgender identities, transsexuals, and travestis, using incorrect pronouns and proposing a single space for trans people within the institution, thereby promoting their segregation. The relationships in this institutional space are marked by power dynamics between professionals and residents, with the latter in a position of submission and the former in a position of authority. It was possible to observe dynamics of body control in this LTCI through mechanisms and technologies of power, mainly disciplinary practices and surveillance of bodies, leading to relationships marked by emotional blunting that hinder not only sexual acts but also emotional experiences and bonding among residents. To control sexual desires, the institution also uses involuntary medicalization practices reminiscent of asylum-like methods.